2004
DOI: 10.1086/421018
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Rubella Vaccination Strategy: Contribution of a Rubella Susceptibility Study of Women of Childbearing Age in Kyrgyzstan, 2001

Abstract: To contribute to the development of a rubella vaccination strategy, we conducted a study to determine age-specific susceptibility among women aged 15-39 years by testing for rubella-specific IgG antibodies. Of 964 women, 13% were found to be susceptible to rubella. Significantly higher susceptibility among women >25 years old was observed. Susceptibility data are important but are not sufficient to develop a vaccination strategy. After considering all available information, we suggested vaccination of women ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Many factors may lead to equivocal results, including waning of antibody titres with time since infection. Since adults are more likely than young people to have been infected many years previously, such waning is consistent with increases in the proportion of antibody test results that are equivocal with increasing age, as seen in some studies[ 36 ]. In such instances, treating equivocal results as positive leads to a more reliable estimate of the force of infection in the past than that obtained by treating equivocal results as negative.…”
Section: Discussionsupporting
confidence: 70%
“…Many factors may lead to equivocal results, including waning of antibody titres with time since infection. Since adults are more likely than young people to have been infected many years previously, such waning is consistent with increases in the proportion of antibody test results that are equivocal with increasing age, as seen in some studies[ 36 ]. In such instances, treating equivocal results as positive leads to a more reliable estimate of the force of infection in the past than that obtained by treating equivocal results as negative.…”
Section: Discussionsupporting
confidence: 70%
“…To achieve elimination, MR immunity gaps among adults in Georgia must be closed. Implementing large-scale SIAs with high coverage is the WHO-recommended approach to rapidly increase population immunity to levels needed to interrupt transmission [23][24][25][26][27][28]. However, previous MR SIAs in Georgia have not been particularly successful [4,6].…”
Section: Epidemiology and Infectionmentioning
confidence: 99%
“…Additionally, approximately 3 to 23% of adults remain susceptible to rubella virus infection in various countries and areas, although studies have shown that a large proportion of unimmunized populations in areas where rubella is endemic are infected and become seropositive before puberty [13,14,15,16]. Dwyer et al, (2001) noted that about 10-25% of non-immunized women of childbearing age are susceptible to rubella virus infection [17].…”
Section: Introductionmentioning
confidence: 99%